Coarse‐grained methods for polymeric materials: enthalpy‐ and entropy‐driven models. (10th May 2013) - Carbone, Paola; Avendaño, Carlos
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>